1997
DOI: 10.1128/jvi.71.8.5849-5860.1997
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a nonconsensus branch point is influenced by an RNA stem-loop structure and is important to confer stability to the herpes simplex virus 2-kilobase latency-associated transcript

Abstract: Herpes simplex virus type 1 latent infection in sensory neurons is characterized by the highly restricted transcription of viral genes. The latency-associated transcripts (LAT) family members are the only transcripts that can be identified in large amounts in latently infected cells. The most abundant LAT species is a 2-kb RNA that results from splicing of a rare primary transcript. Analysis of a LAT mutant virus (TB1) in cell culture revealed an aberrant splicing pattern and production of a stable small (0.95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…This demonstrated that the outer splice sites are normally active in lytic and latent infection, which supports the interpretation of our mutational studies that our splice site mutations abolished LAT expression by disrupting normal splicing. Using other primer pairs, we have also amplified and sequenced additional splice junctions from latent infections, demonstrating the mixed pairing of outer and inner splice sites of opposite polarity (data not shown) and identifying a minor splice acceptor previously observed in transient transfection studies with a LAT minigene (37) (Fig. 5B).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…This demonstrated that the outer splice sites are normally active in lytic and latent infection, which supports the interpretation of our mutational studies that our splice site mutations abolished LAT expression by disrupting normal splicing. Using other primer pairs, we have also amplified and sequenced additional splice junctions from latent infections, demonstrating the mixed pairing of outer and inner splice sites of opposite polarity (data not shown) and identifying a minor splice acceptor previously observed in transient transfection studies with a LAT minigene (37) (Fig. 5B).…”
Section: Resultssupporting
confidence: 60%
“…Considerable evidence now exists that lytic 2-kb LAT is a lariat-shaped molecule, as expected for an excised intron (46,68). However, most excised introns are rapidly degraded while the LATs are stable (37,46). It has been shown by hybridization with short oligonucleotide probes that the 2-kb LAT does not extend fully to the external splice acceptor site (46,52,68), suggesting that this excised intron is targeted by a 3Ј-exonucleolytic activity like most excised introns, but that this activity encounters a barrier just inside the intron.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The nomenclature of these RNAs reflects their abundance and ease of detection within experimental systems. The inefficiently debranched stable lariat structure of the major LATs produced during splicing probably explains their abundance (Farrell et al ., ; Wu et al ., , ; Krummenacher et al ., ; Rødahl & Haarr, ). In contrast, the 8.3 kb minor LAT transcript and its 6.3 kb exon are difficult to reliably detect without more sensitive in situ hybridization (ISH) or RT‐PCR methods (Rock et al ., ; Deatly et al ., ; Zwaagstra et al ., ; Devi‐Rao et al ., ; Arthur et al ., ).…”
Section: Virus Transcription During Latencymentioning
confidence: 99%